Are the well-fed less thirsty? Effects of drought and salinity on New Zealand mangroves. (12th July 2021) - Ravi, Sridevi; Bader, Martin K-F; Young, Tim; Duxbury, Mark; Clearwater, Michael; Macinnis-Ng, Cate; Leuzinger, Sebastian
Abstract: Despite a large number of studies examining the effects of abiotic stress factors on plants, the mechanistic explanations of drought-induced tree mortality remain inconclusive and even less is known about how multiple stressors interact. The role of non-structural carbohydrates (NSCs) in preventing or postponing drought mortality is gaining attention. Here, we tested the role of NSCs in mitigating the effects of drought and salinity in New Zealand mangroves, Avicennia marina subsp. australasica . We experimentally manipulated plant NSC levels, prior to subjecting them to combinations of drought and salinity. Plant growth and survival rates were 2- and 3-fold higher in the high-NSC (H-NSC) group than in the low-NSC (L-NSC) group under high salinity and drought conditions, respectively. After 12 weeks under high salinity–high drought conditions, the H-NSC group showed higher stem hydraulic conductivity (281 ± 50 mmol cm −1 s −1 MPa −1 ) compared with the L-NSC group (134 ± 40 mmol cm −1 s −1 MPa −1 ). Although starch levels remained relatively constant, we found a 20% increase in soluble sugars in the stems of H-NSC group under high drought and high salinity in week 8 compared with week 12. Our results suggest (i) an important role of NSCs in mitigating the effects of low soil water potential caused by drought and salinity, and (ii) sink-limited growth under conditions of combined salinity and drought.